2023
DOI: 10.1039/d2ta09276j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in catalyst design and activity enhancement induced by a magnetic field for electrocatalysis

Abstract: In recent years, researchers have extensively studied the intrinsic potential of electrocatalysts to improve their performance. An emerging field that has gained significant attention is the use of magnetic fields...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 189 publications
0
11
0
Order By: Relevance
“…Spin effects in radical reactions are well established. Magnetic field effects on chemical reactions have been considered by Turro and Kraeutler, Steiner and Ulrich, and Buchachenko . In electrochemistry, magnetic effects are a long established research domain. Magnetic effects on transport are well developed for uniform and gradient magnetic fields. , Although a magnetic effect on electron transfer might be anticipated based on the coupling of current and electrical and magnetic fields and gradients in electromagnetic theory, magnetic effects on electron transfer are not well resolved. Careful studies in uniform magnetic fields have identified no impacts on electron transfer for electrode materials with or without unpaired electrons. , Here, magnetic gradients are identified as a critical component in the magnetoelectrocatalysis of HER.…”
Section: Discussionmentioning
confidence: 99%
“…Spin effects in radical reactions are well established. Magnetic field effects on chemical reactions have been considered by Turro and Kraeutler, Steiner and Ulrich, and Buchachenko . In electrochemistry, magnetic effects are a long established research domain. Magnetic effects on transport are well developed for uniform and gradient magnetic fields. , Although a magnetic effect on electron transfer might be anticipated based on the coupling of current and electrical and magnetic fields and gradients in electromagnetic theory, magnetic effects on electron transfer are not well resolved. Careful studies in uniform magnetic fields have identified no impacts on electron transfer for electrode materials with or without unpaired electrons. , Here, magnetic gradients are identified as a critical component in the magnetoelectrocatalysis of HER.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] On the other hand, the external field delivers the ability to modify the intrinsic electronic spin states and optimize the electrocatalytic properties. [24][25][26][27] Recently, ferromagnetic materials with many spin-related applications, including inorganic oxide materials, atom-based and organic materials, have become theoretical and experimental models to study spin-regulated electrocatalysis. Therefore, alignment of the directed spin and magnetic moment may be beneficial to lower the energy barrier or overcome spin suppression, i.e., spin electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The spin-sensitive feature of the OER arises from the spin state transition: from singlet-state reactants OH − /H 2 O (diamagnetic) to triplet-state products O 2 (paramagnetic). 15,16 The transition from a singlet to a triplet state in spin reconstruction necessitates overcoming an energy barrier of approximately 1.0 eV, leading to a significant overpotential. 17 erations, the modification of the electron spin by an external magnetic field has garnered significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have transcended the aforementioned paradigm, shedding light on the inadvertently overlooked spin interaction between catalysts and oxygenated intermediates in the OER process. , The spin-sensitive feature of the OER arises from the spin state transition: from singlet-state reactants OH – /H 2 O (diamagnetic) to triplet-state products O 2 (paramagnetic). , The transition from a singlet to a triplet state in spin reconstruction necessitates overcoming an energy barrier of approximately 1.0 eV, leading to a significant overpotential . Building upon the previously mentioned considerations, the modification of the electron spin by an external magnetic field has garnered significant attention. , For example, Garcés-Pineda and co-workers have demonstrated the beneficial impact of external magnetic fields in reducing overpotential.…”
Section: Introductionmentioning
confidence: 99%